Public Accounting Firm Switching on the Companies Listed in IDX (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
The purpose of this study is to determine the probability of the changes of upgrade, downgrade, and same grade public accounting firms predicted by prior audit opinion, growth rate of the client, public ownership and financial distress. The population in this study is manufacturing companies listed in Indonesia Stock Exchange for year of 2010-2015 which consist of 144 companies. The sampling technique is a purposive sampling method which results for 24 companies. Analysis method uses descriptive statistics and multinomial logistic regression analysis. The results of this study showed that the variables of prior audit opinion, growth rate of client, and financial distress could predict the probability of the changes of upgrade, downgrade and same grade public accounting firms. Meanwhile, public ownership variable could not predict the probability of the changes of upgrade, downgrade and same grade public accounting firms. It can be concluded that to predict the change of public accountant office can be performed by paying attention to prior audit opinion, client’s growth rate, and financial distress.